2002
DOI: 10.1021/jf0108462
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Virgin Olive Oil. 1. Autoxidation Studies

Abstract: Virgin olive oil samples with similar oxidative stabilities and fatty acid compositions were stored for 24 months. Changes in the lipid substrate were followed by peroxide value and K(232) measurements. HPLC was used to evaluate changes in the alpha-tocopherol, pigment, and squalene contents. Total polar phenol content was measured colorimetrically. The loss of alpha-tocopherol and carotenoids was comparable with that of polar phenol content, suggesting an active participation in autoxidation. The limited role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
129
0
11

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 18 publications
14
129
0
11
Order By: Relevance
“…These results are also in conformity with those indicating a squalene loss ranged between 26-47 for virgin olive oils stored at room temperature 25 for 6 months of storage in the dark 21 but not with the low reduction 10 referred to by Psomiadou, & Tsimidou 19 . On the other hand, Rastrelli, et al 22 showed that squalene content in Scalicelle 45 and Terzer 51.5 olive oil deceased significantly only after 6 months in half-empty bottles, while, they claimed that diffused lighting does not appear to play a significant role in the squalene degradation Scalicelle, 19.3 , and Terzera, 23.8 , after 12 months of storage in the filled colorless bottles at diffused lighting 22 .…”
Section: Mg Kg 1 Of Chlorophyll Pigments Extracted Fromsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are also in conformity with those indicating a squalene loss ranged between 26-47 for virgin olive oils stored at room temperature 25 for 6 months of storage in the dark 21 but not with the low reduction 10 referred to by Psomiadou, & Tsimidou 19 . On the other hand, Rastrelli, et al 22 showed that squalene content in Scalicelle 45 and Terzer 51.5 olive oil deceased significantly only after 6 months in half-empty bottles, while, they claimed that diffused lighting does not appear to play a significant role in the squalene degradation Scalicelle, 19.3 , and Terzera, 23.8 , after 12 months of storage in the filled colorless bottles at diffused lighting 22 .…”
Section: Mg Kg 1 Of Chlorophyll Pigments Extracted Fromsupporting
confidence: 90%
“…2 18 , which reported that enrichment of refined olive oil with phenolic compounds and chlorophyll pigments rich extract recovered from Chemlali olive leaves resulted in an appreciable resistance to oxidative deterioration. In addition, Psomiadou, & Tsimidou 19 claimed that squalene had a protective effect on the oxidative stability of olive oil due to the products of squalene oxidation are quite stable and would not be further involved in propagation reactions.…”
Section: Quality Indicesmentioning
confidence: 99%
“…In contrast, the mechanism for the formation of 13 2 -OH-pheophytin is afected by the composition of VOO, which is logical due to the presence of compounds that act as radical scavengers in VOO that can partially inhibit the mechanism of degradation by free radicals. " clear relationship between the content of radical scavengers and the formation of OH-phy in VOO stored in darkness has not been found [92]. " marked efect of temperature has been discovered for the thermodegradation reactions of pigments in VOO, and perhaps contrary to…”
Section: Figurementioning
confidence: 98%
“…It has been found that phenolic compounds and carotenoids decrease autoxidation in oil, while tocopherols, chlorophylls and phospholipids demonstrate both antioxidant and prooxidant activity depending on the oil system and storage conditions 18 . However, the vitamers of vitamin E are in general important natural antioxidants in foods because they have the ability to block the propagation of radical reactions although the different vitamers vary widely in activity.The oil antioxidant content in VOO depends on the cultivar, fruit ripening stage, agroclimatic conditions and olive growing techniques 19,20 , and provides information about the oil s oxidative status 21,22 .…”
Section: A N Franco T G-díaz J Sánchez Et Almentioning
confidence: 99%